1979
DOI: 10.2190/vjpr-dhlj-uleg-q2ed
|View full text |Cite
|
Sign up to set email alerts
|

Are Psychiatric Consultants' Recommendations Followed?

Abstract: The extent of adherence to psychiatric consultants' recommendations was calculated through a review of charts. All charts of patients seen in Psychiatric consultation from May 1976 to April 1977 were reviewed and a total of 273 charts contained scoreable consultant recommendations. Recommendations were scored as either actively followed, passively followed or not followed. Results are reported for the extent of adherence 1) between different types of recommendations (medications, disposition, etc.), 2) between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The result in this study is considerably better and it is an equivalent sample. It is closer to that of 77.7% found by Billowitz and Friedson [39] and approaches the figure reported by Van Dyke at al [6] of 90%. However, those studies did not have operational criteria for concordance.…”
Section: Discussionsupporting
confidence: 90%
“…The result in this study is considerably better and it is an equivalent sample. It is closer to that of 77.7% found by Billowitz and Friedson [39] and approaches the figure reported by Van Dyke at al [6] of 90%. However, those studies did not have operational criteria for concordance.…”
Section: Discussionsupporting
confidence: 90%
“…The psychiatric C–L service could provide special knowledge about central nervous system complications after transplant and drug interactions between immunosuppressant and psychotropic medication 8,9 . But are recommendations from psychiatric consultation followed? 10,11 It has been reported that the surgeon has the highest concordance rate (62.3%) with the recommended psychotropic medications among all consultees in Taiwan 12 . The patients with post‐transplant psychiatric consultation are different in some aspects from other medical–surgical consultation inpatients 13 .…”
mentioning
confidence: 99%
“…One study (n=394) reported better adherence by surgeons when compared to internists [4]; two other studies (combined n=1345) reported less adherence by surgeons and gynecologists when compared to internists [6,7]. A fourth study (n=90) reported no difference between the requesting physicians' discipline, with the exception of less adherence by surgeons [11].…”
Section: Consultee-related Variablesmentioning
confidence: 99%
“…All 18 included studies were retrospective cohort studies carried out in order to provide a naturalistic description of clinical practice [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. All these studies can be classified as type C studies according to the grades of recommendation as formulated by the Oxford Centre for Evidence-Based Medicine.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation